The Role of Marketing Management in Enhancing Patient Satisfaction and Loyalty in Hospital Services - Muthilaras Febiena; Devita Intania Putri Gunadi; Andika Zidane Eldaputra (Lentera Ilmu Nusantara, 2026)
Marketing management plays an important role in improving hospital competitiveness amid increasingly intense competition in healthcare services. Hospitals are not only required to provide high-quality medical services but also to meet patient needs and expectations through appropriate marketing strategies. This article aims to analyze the implementation of marketing management in improving patient satisfaction and loyalty in hospitals. The method used is a literature study by reviewing various relevant scientific sources. The results indicate that patient-oriented marketing strategies, service quality improvement, utilization of digital media, and effective patient relationship management can enhance patient satisfaction and loyalty. Therefore, marketing management is an essential factor in supporting the success and sustainability of hospital services. This article contributes to strengthening the understanding of how patient-oriented marketing strategies can support hospital competitiveness and long-term patient loyalty.